Fostering Self-Assessment in English Learning with a Generative AI Platform: A Case of Quizizz AI - Kiki Juli Anggoro; Damar Isti Pratiwi (Studies in Self-Access Learning Journal)
The incorporation of Generative AI and platforms like Quizizz holds immense potential to deliver substantial benefits to both English students and teachers. Students can readily create their interactive self-assessment tools, allowing them to monitor their learning progress independently. Meanwhile, teachers can facilitate and enhance students’ independent learning, easing their workload, offering personalized insights, and boosting student engagement. Additionally, Quizizz AI can serve as a valuable resource for teachers looking to advance their professional development. Importantly, both students and teachers can explore new concepts at their own pace without the fear of judgment from others. While the platform offers numerous advantages for both educators and learners, several enhancements could render it an even more potent tool. By diversifying the types of AI-generated questions, the platform could create a wider range of activities targeting various English language skills. Furthermore, expanding the variety of AI-generated responses, such as voice or video, could facilitate the practice of productive skills like speaking. Additionally, written-text responses could promote writing skills. To further enrich the learning experience, the integration of AI for checking and providing personalized feedback on these responses might be considered.